Keith McNeal collection. Iya Rodney's Feast - Keith McNeal - McNeal, Keith E.; Rodney, Iya; Banyan Archives (Trinidad and Tobago : Banyan Archive, 2000)
Orisha feast and Bull sacrifice with Trinidad Orisha's oldest priestess, Iya Rodney who has been officiating the rituals since her ordination during the 1920s.
Title from resource description page (viewed December 8, 2022).
In English.
Keywords: Orisha religion -- Trinidad and Tobago; Fasts and feasts -- Trinidad and Tobago; Trinidad and Tobago -- Social life and customs; Trinidad and Tobago -- Religious life and customs; Orisha (Religion) -- Trinité-et-Tobago.; Trinité-et-Tobago -- Mœurs et coutumes; Trinité-et-Tobago -- Vie religieuse; Fasts and feasts; Manners and customs; Orisha religion; Trinidad and Tobago; documentary film; Documentary films; Unedited footage; Documentary films; Unedited footage; Documentaires